Zirconium composite oxide and method for producing zirconium composite oxide
Patent Information
- Application Number
- CN202280050722.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-28
- Filing Date
- 2022-07-26
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-07-26
AI Technical Summary
现有催化剂在富燃控制中暴露于高温时比表面积降低,导致净化性能下降,无法满足减少CO2排放的需求。
A zirconium composite oxide containing 5% to 50% by mass of yttrium oxide and cerium oxide is used. After heating at 1250°C for 10 hours, the specific surface area is 3.0 m²/g to 20.0 m²/g. A reaction solution containing basic zirconium sulfate is generated by mixing sulfuric acid chlorinating agent with zirconium salt solution and composite hydroxide. Cerium salt solution or compound is added to improve the sintering inhibition effect.
Even at temperatures exceeding 1200℃, zirconium composite oxides can maintain a high specific surface area and pore volume, ensuring the oxygen storage performance of both the catalyst and the precious metal catalyst, improving thermal stability and thermal stability under heat load, and enhancing the catalyst's exhaust gas purification performance.
Smart Images

Figure BDA0004670530200000201
Abstract
Description
Technical Field
[0001] This invention relates to a zirconium composite oxide and a method for manufacturing the zirconium composite oxide. Background Technology
[0002] There has always been a strong demand to improve fuel efficiency in automobiles in order to reduce CO2 emissions. On the other hand, in the engine control of automobiles, in order to maximize the purification performance of the catalyst, excessive fuel injection is required, which is known as fuel-rich combustion.
[0003] Patent Document 1 discloses a composition comprising zirconium dioxide and cerium oxide, which, after being heated at 1200°C for more than 10 hours, has an apparent surface area of about 1.0 to about 6.0 m². 2 / g (especially with reference to claim 1).
[0004] Patent document 2 discloses a composition consisting of an oxide of zirconium, cerium, lanthanum, and any one of the rare earth elements yttrium, samarium, or gadolinium, which has a specific surface area of 7 m² after being heated at 1200°C for 10 hours. 2 / g or more 12m 2 / g or less (especially with reference to claim 1, the embodiment).
[0005] Patent document 3 discloses a composition based on zirconium oxide, cerium oxide, and yttrium oxide, which, after being calcined at 1150°C for 10 hours, has a particle size of at least 15 μm. 2 The specific surface area per g (especially referring to claim 1) is 12 m² after heating at 1200°C for 10 hours. 2 / g or less (especially refer to the examples).
[0006] Patent document 4 discloses a composition comprising zirconium, cerium, and lanthanum, which has a specific surface area of 35–50 m² after being heated in air at 1100°C for 4 hours. 2 / g (especially with reference to claim 1).
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Publication No. 2017-532278
[0010] Patent Document 2: Description of European Patent No. 2024084
[0011] Patent Document 3: Japanese Patent Publication No. 2009-526729
[0012] Patent Document 4: U.S. Patent Application Publication No. 2019 / 0134608 Summary of the Invention
[0013] The problem the invention aims to solve
[0014] Rich fuel delivery leads to decreased fuel efficiency due to excessive fuel supply. Therefore, it is believed that in the future development of vehicles that prioritize reducing CO2 emissions, engine control with less fuel-rich engines will become the mainstream.
[0015] When the fuel-rich content decreases, the catalyst and its support are exposed to higher temperatures. This means an increased thermal load on the catalyst and its support. As the thermal load increases, the catalyst support sinters. Sintering of the support leads to a decrease in its specific surface area. This decrease in surface area leads to the sintering of the noble metal (catalyst) it supports. When the noble metal sinters, the catalyst activity decreases, and the catalyst's exhaust gas purification performance deteriorates.
[0016] Traditionally, catalysts used in fuel-rich control only needed to withstand a heat load of 1100°C. However, in fuel-rich reduction control, a higher specific surface area is required after exposure to temperatures exceeding 1200°C.
[0017] The present invention was made in view of the above-mentioned problems, and its object is to provide a zirconium composite oxide that can maintain a high specific surface area even when exposed to higher temperatures exceeding 1200°C. Another object is to provide a method for manufacturing the zirconium composite oxide.
[0018] Solution to the problem
[0019] The inventors conducted in-depth research on zirconium composite oxides. They discovered that the aforementioned problems could be solved by adopting the following configuration, thus completing this invention.
[0020] That is, the zirconium composite oxide in this invention is characterized by comprising:
[0021] Yttrium oxide of 5% to 50% by mass, and
[0022] Cerium oxide,
[0023] The specific surface area after heating at 1250℃ for 10 hours is 3.0 m². 2 / g or more 20.0m 2 / g or less.
[0024] According to the aforementioned composition, since it includes a high content of yttrium oxide (5% by mass or more), sintering can be suppressed even when exposed to high temperatures. Furthermore, since it includes cerium oxide, sintering can also be suppressed even when exposed to high temperatures.
[0025] In addition, the specific surface area after heating at 1250℃ for 10 hours is 3.0 m². 2With a specific surface area of over / g, it can be assumed that it has a high specific surface area even when exposed to higher temperatures exceeding 1200°C.
[0026] Thus, according to the aforementioned composition, due to the inclusion of a high content of yttrium oxide (5% by mass) and cerium oxide which has a sintering-inhibiting effect, the specific surface area after heating at 1250°C for 10 hours is 3.0 m². 2 With a surface area of over / g, it can maintain a high specific surface area even when exposed to higher temperatures exceeding 1200°C.
[0027] It should be noted that in the compositions of Patent Documents 1 to 4, it is disclosed that the specific surface area after exposure to 1100°C is above a certain level, and the specific surface area after exposure to 1200°C is above a certain level. However, in the compositions of Patent Documents 1 to 4, the specific surface area after heating at 1250°C for 10 hours cannot reach 3.0 m². 2 / g or more.
[0028] In the aforementioned configuration, the yttrium oxide content is preferably 40% by mass or less.
[0029] When the yttrium oxide content is less than 40% by mass, it may contain appropriate amounts of cerium oxide and zirconium dioxide required as oxygen-absorbing and oxygen-releasing materials.
[0030] In the aforementioned composition, the content of cerium oxide is preferably 5% by mass or more and 50% by mass or less.
[0031] When the content of cerium oxide is more than 5% by mass and less than 50% by mass, a higher sintering inhibition effect can be obtained.
[0032] In the aforementioned composition, it is preferable to include one or more oxides selected from rare earth elements other than cerium and yttrium.
[0033] When more than one oxide selected from rare earth elements other than cerium and yttrium is included, a higher sintering inhibition effect can be obtained.
[0034] In the aforementioned configuration, the oxide is preferably one or more oxides selected from the group consisting of lanthanum oxide, neodymium oxide, and praseodymium oxide.
[0035] When the oxide is one or more oxides selected from the group consisting of lanthanum oxide, neodymium oxide, and praseodymium oxide, a higher sintering inhibition effect can be obtained.
[0036] In the aforementioned configuration, the content of lanthanum oxide is preferably 1% by mass or more and 30% by mass or less.
[0037] When the content of lanthanum oxide is more than 1% by mass and less than 30% by mass, a higher sintering inhibition effect can be obtained.
[0038] In the aforementioned configuration, the content of neodymium oxide is preferably 1% by mass or more and 30% by mass or less.
[0039] When the neodymium oxide content is more than 1% by mass and less than 30% by mass, a higher sintering inhibition effect can be obtained.
[0040] In the aforementioned composition, the content of praseodymium oxide is preferably 1% by mass or more and 30% by mass or less.
[0041] When the content of praseodymium oxide is more than 1% by mass and less than 30% by mass, a higher sintering inhibition effect can be obtained.
[0042] In the aforementioned composition, it is preferable to include stabilized zirconium oxide containing 20 mol% to 30 mol% of yttrium oxide.
[0043] The yttrium oxide content in stabilized zirconia is 23 mol%, at which point the melting point is highest. Therefore, when stabilized zirconia includes 20–30 mol% or more of yttrium oxide and has a high melting point, a higher sintering inhibition effect can be obtained.
[0044] In the aforementioned configuration, the specific surface area after heating at 1200°C for 10 hours is preferably 12.0 m². 2 / g or above 40.0m 2 / g or less.
[0045] The specific surface area after heating at 1200℃ for 10 hours is 12.0 m². 2 When the surface area is above / g, it can maintain a high specific surface area even when exposed to 1200℃.
[0046] In the aforementioned configuration, the pore volume is preferably 0.4 ml / g or more and 1.0 ml / g or less.
[0047] When the pore volume is between 0.4 ml / g and 1.0 ml / g, it exhibits a high pore volume before exposure to high temperatures. Because it has a high pore volume before exposure to high temperatures, the pore volume after exposure to high temperatures can be further increased. Because the pore volume after exposure to high temperatures can be further increased, the specific surface area after exposure to high temperatures can be further increased.
[0048] In the aforementioned configuration, the oxygen storage material of the catalyst for exhaust gas purification is preferred.
[0049] Since the zirconium composite oxide has a high sintering inhibition effect when it is used as an oxygen storage material in a catalyst for waste gas purification, it can suppress the reduction of waste gas purification performance.
[0050] Furthermore, the method for manufacturing zirconium composite oxide in this invention is characterized by comprising:
[0051] The first step is to obtain a composite hydroxide comprising Zr and Y, which is at more than 20 mol% and less than 30 mol% as oxides;
[0052] The second step involves mixing a mixture of sulfuric acid chlorinating agent and zirconium salt solution with the composite hydroxide to obtain a reaction solution containing basic zirconium sulfate; and
[0053] In the third step, a cerium salt solution or compound is added to the reaction solution containing basic zirconium sulfate.
[0054] According to the aforementioned composition, a mixture of sulfuric acid chlorinating agent and zirconium salt solution and the composite hydroxide are mixed to obtain a reaction solution containing basic zirconium sulfate. Therefore, the resulting reaction solution containing basic zirconium sulfate forms fine pores through the formation of zirconium sulfate, resulting in a high dispersion of the composite hydroxide within the zirconium sulfate.
[0055] The composite hydroxide is sintered to form stabilized zirconium oxide (hereinafter also referred to as "YSZ"). Because the composite hydroxide contains a relatively high amount of yttrium, the stabilized zirconium oxide with a high melting point is highly dispersed in the final zirconium composite oxide. This results in a high degree of sintering inhibition in the final zirconium composite oxide.
[0056] Furthermore, since a cerium salt solution or compound is added to the reaction solution containing basic zirconium sulfate, the resulting zirconium composite oxide includes cerium oxide, which has a sintering inhibition effect. As a result, the final zirconium composite oxide can achieve a higher sintering inhibition effect.
[0057] In the aforementioned configuration, the third step preferably includes: further adding a salt solution or compound of one or more metals selected from rare earth elements other than cerium and yttrium to a reaction solution containing basic zirconium sulfate.
[0058] When the third step includes adding a salt solution or compound of one or more metals selected from rare earth elements other than cerium and yttrium to a reaction solution containing basic zirconium sulfate, the resulting zirconium composite oxide further includes oxides of rare earth elements other than cerium and yttrium that have sintering inhibition effects. This results in the final zirconium composite oxide achieving an even higher sintering inhibition effect.
[0059] Invention Effects
[0060] According to the present invention, a zirconium composite oxide can be provided that maintains a high specific surface area even when exposed to temperatures exceeding 1200°C. A method for manufacturing the zirconium composite oxide can also be provided. Detailed Implementation
[0061] The embodiments of the present invention will be described below. However, the present invention is not limited to these embodiments. It should be noted that, in this specification, zirconium oxide refers to ordinary zirconium oxide, including less than 10% by mass of impurity metal compounds, which include hafnium oxide.
[0062] [Zirconium composite oxide]
[0063] The zirconium composite oxide in this embodiment is a composite oxide with zirconium oxide as an essential component and other oxides (other metal oxides), which will be described in detail below. The application of the zirconium composite oxide in this embodiment is not particularly limited; it can be used as an oxygen storage material for catalysts used in waste gas purification. When used as an oxygen storage material for catalysts used in waste gas purification, the catalyst that can be supported in the oxygen storage material can be a noble metal catalyst, etc.
[0064] Specific surface area
[0065] [1. Specific surface area after heating at 1250℃ for 10 hours]
[0066] The specific surface area of the zirconium composite oxide after heating at 1250℃ for 10 hours is 3.0 m². 2 / g or more 20.0m 2 / g or less. The specific surface area is 3.0 m² after heating at 1250℃ for 10 hours. 2 With a specific surface area of over / g, it can be assumed that even when exposed to higher temperatures exceeding 1200°C, it can still possess a high specific surface area.
[0067] The specific surface area after heating at 1250°C for 10 hours is preferably 4 m². 2 / g or more, preferably 5m 2 / g or more, further preferably 6m 2 / g or more, especially preferably 8m 2 / g or more.
[0068] The specific surface area after heating at 1250°C for 10 hours is preferably as large as possible, for example, 18 m². 2 / g or less, 15m 2 / g or less, 14m 2 / g and below, etc.
[0069] [2. Specific surface area after heating at 1200℃ for 10 hours]
[0070] The specific surface area of the zirconium composite oxide after heating at 1200°C for 10 hours is preferably 12.0 m². 2 / g or above 40.0m 2 The specific surface area is below / g. After heating at 1200℃ for 10 hours, it is 12.0 m². 2 When the surface area is above / g, it can maintain a high specific surface area even when exposed to 1200℃.
[0071] The specific surface area after heating at 1200°C for 10 hours is preferably 12.2 m². 2 / g or more, preferably 12.5m 2 / g or more, further preferably 13m 2 / g or more, especially preferably 14m 2 / g or more.
[0072] The specific surface area after heating at 1200°C for 10 hours is preferably as large as possible, for example, 35 m². 2 / g or less, 30m 2 / g or less, 25m 2 / g or less, 20m 2 / g and below, etc.
[0073] [3. Specific surface area after heating at 1200℃ for 3 hours]
[0074] The specific surface area of the zirconium composite oxide after heating at 1200°C for 3 hours is preferably 14 m². 2 / g or more 50m 2 / g or less. The specific surface area after heating at 1200℃ for 3 hours is 14m². 2 When the concentration is above a certain level, it can be used as a catalyst support.
[0075] The specific surface area after heating at 1200°C for 3 hours is preferably 14.5 m². 2 / g or more, preferably 15m 2 / g or more, further preferably 16m 2 / g or more.
[0076] The specific surface area after heating at 1200°C for 3 hours is preferably as large as possible, for example, 45 m². 2 / g or less, 40m 2 / g or less, 35m 2 / g or less, 30m 2 / g or less.
[0077] [4. Specific surface area after heating at 1100℃ for 3 hours]
[0078] The specific surface area of the zirconium composite oxide after heating at 1100°C for 3 hours is preferably 20 m². 2 / g or more 60m 2 / g or less. The specific surface area after heating at 1100℃ for 3 hours is 20m². 2 When the concentration is above a certain level, it can be used as a catalyst support.
[0079] The specific surface area after heating at 1100°C for 3 hours is preferably 22 m². 2 / g or more, preferably 23m 2 / g or more, further preferably 24m 2 / g or more.
[0080] The specific surface area after heating at 1100°C for 3 hours is preferably as large as possible, for example, 55 m². 2 / g or less, 50m 2 / g or less, 45m 2 / g and below, etc.
[0081] [5. Specific surface area after heating at 1000℃ for 3 hours]
[0082] The specific surface area of the zirconium composite oxide after heating at 1000°C for 3 hours is preferably 30 m². 2 / g or more 80m 2 / g or less. The specific surface area after heating at 1000℃ for 3 hours is 30m². 2 When the concentration is above a certain level, it can be used as a catalyst support.
[0083] The specific surface area after heating at 1000°C for 3 hours is preferably 33 m². 2 / g or more, preferably 36m 2 / g or more, further preferably 38m 2 / g or more.
[0084] The specific surface area after heating at 1000°C for 3 hours is preferably as large as possible, for example, 75 m². 2 / g or less, 70m 2 / g or less, 65m 2 / g and below, etc.
[0085] [6. Initial specific surface area]
[0086] The specific surface area (initial specific surface area) of the zirconium composite oxide is preferably 40 m². 2 / g or more. It can be considered that when the specific surface area is 40m², 2At a specific surface area of / g or higher, it exhibits a high specific surface area before exposure to high temperatures. Because of this high specific surface area before exposure to high temperatures, the specific surface area after exposure to high temperatures can be further increased. Here, specific surface area (initial specific surface area) refers to the specific surface area after the zirconium composite oxide is manufactured, before any heat treatment or pulverization treatment.
[0087] The specific surface area is preferably 40m². 2 / g or more, preferably 45m 2 / g or more, more preferably 50m 2 / g or more, especially preferably 55m 2 / g or more, especially preferably 60m 2 / g or more.
[0088] The specific surface area is preferably as large as possible, for example, 110 m². 2 / g or less, 100m 2 / g or less, 90m 2 / g and below, etc.
[0089] The specific surface area after heating at 1250°C for 10 hours, the specific surface area after heating at 1200°C for 10 hours, the specific surface area after heating at 1200°C for 3 hours, the specific surface area after heating at 1100°C for 3 hours, the specific surface area after heating at 1000°C for 3 hours, and the specific surface area (initial specific surface area) refer to the values obtained by the method described in the embodiments.
[0090] <Fine Pore Volume>
[0091] [1. Pore volume after heating at 1250℃ for 10 hours]
[0092] In this embodiment, the micropore volume of the zirconium composite oxide after heating at 1250°C for 10 hours is preferably 0.02 ml / g or more. It can be considered that when the micropore volume after heating at 1250°C for 10 hours is 0.02 ml / g or more, the micropores will shrink very little even when exposed to high temperatures. Therefore, the specific surface area after heating at 1250°C for 10 hours can be further increased.
[0093] The pore volume after heating at 1250°C for 10 hours is preferably 0.03 ml / g or more, more preferably 0.04 ml / g or more, even more preferably 0.05 ml / g or more, particularly preferably 0.06 ml / g, especially preferably 0.07 ml / g, and even more preferably 0.10 ml / g.
[0094] The pore volume after heating at 1250°C for 10 hours is preferably as large as possible, for example, less than 0.4 ml / g, less than 0.3 ml / g, less than 0.25 ml / g, less than 0.20 ml / g, etc.
[0095] [2. Initial pore volume]
[0096] In this embodiment, the micropore volume (initial micropore volume) of the zirconium composite oxide is preferably 0.4 ml / g or more. When the micropore volume is 0.4 ml / g or more, it has a high micropore volume before exposure to high temperature. Since it has a high micropore volume before exposure to high temperature, the micropore volume after exposure to high temperature can be further increased. Since the micropore volume after exposure to high temperature can be further increased, the specific surface area after exposure to high temperature can be further increased.
[0097] The pore volume is preferably 0.4 ml / g or more, more preferably 0.45 ml / g or more, and even more preferably 0.5 ml / g or more.
[0098] The pore volume is preferably as large as possible, for example, less than 1.0 ml / g, less than 0.9 ml / g, less than 0.8 ml / g, etc.
[0099] For details on the method for calculating the pore volume, please refer to the method described in the embodiment.
[0100] <Particle size>
[0101] The particle size D of the zirconium composite oxide 50 Preferably, the particle size is between 0.1 μm and 100 μm. The particle size D... 50 More preferably, the micrometer is 0.5 μm or more and 50 μm or less.
[0102] <Composition>
[0103] The zirconium composite oxide contains zirconium oxide (zirconia). When the total zirconium composite oxide is set to 100% by mass, the zirconium oxide content is preferably 30% by mass or more, more preferably 35% by mass or more, further preferably 40% by mass or more, particularly preferably 43% by mass or more, and especially preferably 45% by mass or more. There is no particular upper limit to the zirconium oxide content, but it is preferably 95% by mass or less, more preferably 92% by mass or less, further preferably 90% by mass or less, especially preferably 85% by mass or less, particularly preferably 80% by mass or less, and most preferably 75% by mass or less. When the zirconium oxide content is 30% by mass or more and 95% by mass or less, it is suitable for use as a catalyst support.
[0104] It should be noted that when the zirconium composite oxide includes stabilized zirconium oxide, the zirconium oxide content in the zirconium composite oxide is the total amount of zirconium oxide constituting stabilized zirconium oxide and other zirconium oxides.
[0105] Relative to the zirconium composite oxide as a whole, the zirconium composite oxide includes yttrium oxide at a content of 5% to 50% by mass. Because it includes a high content of yttrium oxide of 5% or more, sintering can be suppressed even when exposed to high temperatures. Furthermore, since the yttrium oxide content is 50% by mass or less, it can contain the amounts of cerium oxide and zirconium dioxide required as oxygen-absorbing and oxygen-releasing materials.
[0106] It should be noted that when the zirconium composite oxide includes stabilized zirconium oxide, the yttrium content in the zirconium composite oxide includes yttrium oxide that constitutes stabilized zirconium oxide.
[0107] The yttrium oxide content is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass. The yttrium oxide content is preferably 48% by mass or less, more preferably 45% by mass or less, particularly preferably 40% by mass or less, and especially preferably 35% by mass or less.
[0108] The zirconium composite oxide includes cerium oxide. Because it includes cerium oxide, sintering is suppressed even when exposed to high temperatures.
[0109] The content of cerium oxide relative to the total zirconium composite oxide is preferably 5% by mass or more, more preferably 7.5% by mass or more. The content of cerium oxide relative to the total zirconium composite oxide is preferably 50% by mass or less, more preferably 45% by mass or less, and particularly preferably 41% by mass or less. When the content of cerium oxide is 5% by mass or more and 50% by mass or less, a higher sintering inhibition effect can be obtained.
[0110] The zirconium composite oxide preferably comprises one or more oxides selected from rare earth elements other than cerium and yttrium. Preferably, the zirconium composite oxide does not contain phosphorus (Pm). More preferably, the zirconium composite oxide comprises one or more oxides selected from rare earth elements other than cerium, yttrium, and Pm.
[0111] It should be noted that rare earth elements refer to Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
[0112] When more than one oxide selected from rare earth elements other than cerium and yttrium is included, a higher sintering inhibition effect can be obtained.
[0113] Among rare earth elements other than cerium and yttrium, La (lanthanum), Nd (neodymium), and Pr (praseodymium) are preferred. That is, the zirconium composite oxide preferably contains one or more oxides selected from the group consisting of lanthanum oxide, neodymium oxide, and praseodymium oxide. When the zirconium composite oxide contains one or more oxides selected from the group consisting of lanthanum oxide, neodymium oxide, and praseodymium oxide, a higher sintering inhibition effect can be further obtained.
[0114] Relative to the overall zirconium composite oxide, the content of one or more oxides selected from rare earth elements other than cerium and yttrium is preferably 1% by mass or more, more preferably 3% by mass or more, further preferably 4% by mass or more, and particularly preferably 5% by mass or more. Relative to the overall zirconium composite oxide, the content of one or more oxides selected from rare earth elements other than cerium and yttrium is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, and particularly preferably 10% by mass or less. When the content of one or more oxides selected from rare earth elements other than cerium and yttrium is 1% by mass or more and 30% by mass or less, a higher sintering inhibition effect can be obtained.
[0115] In addition to zirconium oxide and oxides of rare earth elements other than cerium and yttrium, the zirconium composite oxide may also include: selected from
[0116] A) Select one or more oxides from the group consisting of In, Si, P, Sn, Bi, and Zn;
[0117] B) Transition metal oxides (excluding oxides of rare earth elements and noble metals); and
[0118] C) Alkaline earth metal oxides
[0119] Oxides of one or more elements in a group.
[0120] Hereinafter, in this specification, the elements shown in A) to C) will be referred to as "other elements". When the zirconium composite oxide includes oxides of the other elements, when the zirconium composite oxide as a whole is set to 100% by mass, the content of the oxides of the other elements, in terms of oxides, can be 0.1% by mass or more. There is no particular upper limit to the content of the oxides of the other elements, and it can be 20% by mass or less, 10% by mass or less, 7% by mass or less, 5% by mass or less, etc.
[0121] The transition metals may be, for example, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ta, W, etc. The alkaline earth metals may be Mg, Ca, Sr, Ba, etc.
[0122] Furthermore, within the scope of the present invention (e.g., less than 0.5% by mass), the zirconium composite oxide may also contain impurities. These impurities are not particularly limited and may include components contained in the raw materials, components introduced during the manufacturing process, or components not completely removed during the manufacturing process (e.g., SO4, etc.).
[0123] The zirconium composite oxide preferably includes stabilized zirconium oxide containing 20 mol% to 30 mol% yttrium oxide. That is, when the zirconium composite oxide includes stabilized zirconium oxide, the yttrium oxide content in the stabilized zirconium oxide is preferably 20 mol% to 30 mol% relative to the total stabilized zirconium oxide. The yttrium oxide content in the stabilized zirconium oxide is 23 mol%, at which point the melting point is highest. Therefore, when it includes stabilized zirconium oxide containing 20 to 30 mol% or more yttrium oxide and having a high melting point, a higher sintering inhibition effect can be further obtained.
[0124] The content of yttrium oxide contained in the stabilized zirconia is more preferably 22 mol% or more, and even more preferably 24 mol% or more, relative to the stabilized zirconia as a whole.
[0125] The content of yttrium oxide contained in the stabilized zirconia is more preferably 28 mol% or less, and even more preferably 26 mol% or less, relative to the stabilized zirconia as a whole.
[0126] The preferred composition ratio of the zirconium composite oxide can be a combination of (1) to (4) below, with a total amount not exceeding 100%.
[0127] (1) Zirconium dioxide: 30% or more, 95% or less
[0128] Yttrium oxide: 5% to 40%
[0129] Cerium oxide: 5% to 50%
[0130] Rare earth oxides other than yttrium oxide and cerium oxide: 0% to 30%
[0131] Oxides of other elements: 0% to 10%
[0132] (2) Zirconium dioxide: 35% or more, 92% or less
[0133] Yttrium oxide: 10% to 40%
[0134] Cerium oxide: 7.5% to 47.5%
[0135] Rare earth oxides other than yttrium oxide and cerium oxide: 1% to 20%
[0136] Oxides of other elements: 0% to 5%
[0137] (3) Zirconium dioxide: 40% to 90%
[0138] Yttrium oxide: 15% to 37.5%
[0139] Cerium oxide: 10% to 45%
[0140] Rare earth oxides other than yttrium oxide and cerium oxide: 2.5% to 15%
[0141] Oxides of other elements: 0% to 2.5%
[0142] (4) Zirconium dioxide: 43% or more, 85% or less
[0143] Yttrium oxide: 20% to 35%
[0144] Cerium oxide: 12.5% to 41%
[0145] Rare earth oxides other than yttrium oxide and cerium oxide: 4% to 10%
[0146] Oxides of other elements: 0% to 1%
[0147] The zirconium composite oxide according to this embodiment, due to its high content of yttrium oxide (more than 5% by mass) and the inclusion of cerium oxide which has a sintering-inhibiting effect, has a specific surface area of 3.0 m² after heating at 1250°C for 10 hours. 2 With a specific surface area of over / g, it can maintain a high specific surface area even when exposed to higher temperatures exceeding 1200°C.
[0148] [Manufacturing method of zirconium composite oxide]
[0149] Hereinafter, an example of a method for manufacturing zirconium composite oxide will be described. However, the method for manufacturing zirconium composite oxide of the present invention is not limited to the following example.
[0150] The method for manufacturing zirconium composite oxide in this embodiment includes:
[0151] The first step is to obtain a composite hydroxide comprising Zr and Y, which is at more than 20 mol% and less than 30 mol% as oxides;
[0152] The second step involves mixing a mixture of sulfuric acid chlorinating agent and zirconium salt solution with the composite hydroxide to obtain a reaction solution containing basic zirconium sulfate; and
[0153] In the third step, a cerium salt solution or compound is added to the reaction solution containing basic zirconium sulfate.
[0154] <First Process>
[0155] In the method for manufacturing zirconium composite oxide in this embodiment, firstly, a composite hydroxide comprising Zr and Y at a concentration of 20 mol% to 30 mol% as oxide is obtained.
[0156] The composite hydroxide can be obtained by mixing zirconium salt solution and yttrium salt solution.
[0157] Any zirconium salt that provides zirconium ions can be used; for example, zirconium oxynitrate, zirconium oxychloride, and zirconium nitrate can be used. One or more of these zirconium salts can be used. Among them, zirconium oxychloride is preferred from the perspective of higher productivity on an industrial scale.
[0158] The solvent used to prepare the zirconium salt solution should be selected according to the type of zirconium salt. Water (pure water or ion-exchanged water) is generally preferred.
[0159] There are no particular restrictions on the concentration of zirconium salt solutions. Generally speaking, it is best to contain 5 to 250 g (especially 20 to 150 g) of zirconium dioxide (ZrO2) per 1000 g of solvent.
[0160] The yttrium salt solution is not particularly limited, and can be, for example, yttrium chloride solution, yttrium nitrate solution, yttrium acetate solution, etc.
[0161] The solvent in the above yttrium salt solution is not particularly limited; for example, it can be water, ether, ethanol, etc.
[0162] The concentration of the yttrium salt solution is not particularly limited, but is preferably 10 to 20% by mass based on yttrium oxide.
[0163] When mixing zirconium salt solutions and yttrium salt solutions, it is preferable to prepare the solution with a total concentration of ZrO2 and Y2O3, calculated as oxides, of 5 w / v% to 20 w / v%. By setting the concentration to 5 w / v% or higher, the filtration process described below does not require a longer time. Furthermore, by setting the concentration to 20 w / v or lower, it is particularly effective in preventing the precipitation of zirconium and yttrium salts from the solution during winter.
[0164] Furthermore, when mixing the zirconium salt solution and the yttrium salt solution, the content of Y, in terms of oxides, is preferably 20 mol% to 30 mol% relative to the total amount of Zr and Y contained in the resulting composite hydroxide. When the mixing is carried out with a Y content of 20 mol% to 30 mol% in terms of oxides, the content of yttrium oxide in the stabilized zirconium oxide contained in the final zirconium composite oxide can be 20 mol% to 30 mol%.
[0165] It should be noted that after mixing the zirconium salt solution and the yttrium salt solution, an alkali such as NaOH aqueous solution or NH3OH aqueous solution is added to obtain a hydroxide. The alkali is not limited; for example, ammonium hydroxide, ammonium bicarbonate, sodium hydroxide, potassium hydroxide, etc., can be used. However, from an industrial cost perspective, sodium hydroxide is preferred. The amount of alkali added is not particularly limited, as long as it is sufficient to generate a hydroxide precipitate from the mixed solution. Typically, the alkali is added in such a way that the pH of the solution reaches 11 or higher, preferably 12 or higher.
[0166] The above yields a composite hydroxide containing Zr and Y (hereinafter also referred to as "YSZ precursor"). This composite hydroxide contains Zr and Y at a concentration of 20 mol% to 30 mol% (based on Y₂O₃). Then, it is filtered and washed.
[0167] Next, the YSZ precursor is heated to 120℃~180℃, and then subjected to a temperature of 0.2×10⁻⁶. 5 Pa ~ 1.0 × 10 6 Under a pressure of Pa, the YSZ precursor slurry was obtained after maintaining the pressure for 30 to 90 minutes.
[0168] The first process has been explained above.
[0169] <Second Process>
[0170] Next, the mixture of sulfuric acid chlorinating agent and zirconium salt solution and the composite hydroxide (YSZ precursor) is heated to obtain a reaction solution containing basic zirconium sulfate (second step).
[0171] The chlorinating agent for sulfuric acid is not limited, as long as it reacts with zirconium ions to form sulfate (i.e., the reagent that chlorinates sulfuric acid). Examples include sodium sulfate, potassium sulfate, and ammonium sulfate. The chlorinating agent for sulfuric acid can be in any form, such as powder or solution, but a solution (especially an aqueous solution) is preferred. The concentration of the solution can be appropriately set when using a solution.
[0172] Preferably, sulfate (SO4) is used. 2- Sulfuric acid chlorinating agent is added in a ZrO2 / Zr ratio of 0.3 to 0.6. Furthermore, the free acid concentration of the mixture is preferably 0.2 to 2.2 N (specified). Examples of free acid include sulfuric acid, nitric acid, hydrochloric acid, etc. The type of free acid is not limited, but hydrochloric acid is preferred from the perspective of higher productivity on an industrial scale.
[0173] The zirconium salt solution can be the same as the zirconium salt solution described in the first step.
[0174] Basic zirconium sulfate is generated when a sulfuric acid chlorinating agent and a zirconium salt solution are mixed and heated. That is, the mixture contains basic zirconium sulfate. The zirconium salt solution and the sulfuric acid chlorinating agent typically react at temperatures above 65°C to generate basic zirconium sulfate. In this invention, basic zirconium sulfate is generated in an autoclave by adding a mixture of zirconium salt solution and sulfuric acid chlorinating agent to a YSZ precursor slurry at a temperature above 100°C.
[0175] There is no particular limitation on the mixing ratio of the mixture to the composite hydroxide (YSZ precursor), but the preferred ratio is that the yttrium oxide content in the final zirconium composite oxide is more than 5% by mass and less than 40% by mass.
[0176] The mixing time between the mixture and the composite hydroxide is preferably 10 to 60 minutes. By setting the mixing time to 10 to 60 minutes, the generated basic zirconium sulfate can be aged. Basic zirconium sulfate is not limited; for example, it can be an aqueous solution of compounds such as ZrOSO4·ZrO2, 5ZrO2·3SO3, and 7ZrO2·3SO3. It should be noted that basic zirconium sulfate can also be one or a mixture of two or more of these compounds.
[0177] The mixing temperature of the mixture and the composite hydroxide is preferably 110℃~150℃.
[0178] After mixing the mixture and the composite hydroxide, it is typically cooled to below 60°C.
[0179] The cooling temperature is preferably below 50°C, more preferably below 40°C. There is no particular limitation on the lower limit of the cooling temperature; it is preferably a temperature that prevents the reaction solution from freezing, such as above 10°C or above 20°C. The cooling rate does not need to be specially controlled and can be achieved through natural cooling. However, in cases with a large oxide scale, since natural cooling takes time, a heat exchanger or similar device can be used for cooling. In this case, the cooling rate can be appropriately set, for example, within the range of 0.1°C / min to 20°C / min.
[0180] The reaction solution containing basic zirconium sulfate can be obtained from the above.
[0181] The resulting reaction solution containing basic zirconium sulfate forms fine pores through the formation of zirconium sulfate, which makes the composite hydroxide (YSZ precursor) highly dispersed in the zirconium sulfate.
[0182] Because the composite hydroxide contains a significant amount of yttrium, the stable zirconium oxide with a high melting point is highly dispersed in the final zirconium composite oxide. This results in a high degree of sintering inhibition in the final zirconium composite oxide.
[0183] The second process has been explained above.
[0184] <Third Process>
[0185] Then, a cerium salt solution or compound is added to the reaction solution containing basic zirconium sulfate (third step). In the third step, a salt solution or compound of one or more metals selected from rare earth elements other than cerium (including yttrium) may also be added.
[0186] The first and second processes are preferably carried out in a high-pressure autoclave, which facilitates the management of temperature and pressure.
[0187] Next, zirconium hydroxide is generated by neutralizing the reaction solution containing basic zirconium sulfate. Specifically, zirconium hydroxide is obtained by neutralizing the reaction solution containing basic zirconium sulfate with an alkali. The alkali is not limited; for example, ammonium hydroxide, ammonium bicarbonate, sodium hydroxide, potassium hydroxide, etc., can be used. Among these, sodium hydroxide is preferred from an industrial cost perspective.
[0188] The amount of alkali added is not limited, as long as it can generate zirconium hydroxide as a precipitate from the reaction solution containing basic zirconium sulfate. Typically, it is added in such a way that the pH of the solution reaches 11 or higher, preferably 12 or higher.
[0189] After the neutralization reaction, it is preferable to keep the solution containing zirconium hydroxide at 35–60°C for at least 1 hour. This allows the precipitate to mature and facilitates filtration.
[0190] Next, zirconium hydroxide is recovered using solid-liquid separation methods. For example, filtration, centrifugation, and decantation can be employed.
[0191] After recovering zirconium hydroxide, it is preferable to wash the zirconium hydroxide with water to remove any attached impurities.
[0192] Zirconium hydroxide can be dried by natural drying or by heating.
[0193] Next, the zirconium hydroxide is heat-treated (sintered) to obtain zirconium composite oxide. The heat treatment temperature is not particularly limited, but it is preferably around 400–900°C for about 1–5 hours. The heat treatment atmosphere is preferably in the atmosphere or an oxidizing atmosphere.
[0194] Depending on the needs, and to improve operability, the obtained zirconium composite oxide can be subjected to decomposition and condensation treatment (fragmentation treatment).
[0195] The manufacturing method of the zirconium composite oxide in this embodiment has been described above.
[0196] Example
[0197] The present invention will now be described in detail with reference to the embodiments. However, the present invention is not limited to the following embodiments without departing from its spirit. It should be noted that in the zirconium composite oxides obtained in the embodiments and comparative examples, hafnium oxide contains 1.3 to 2.5% by mass (calculated by the following formula (X)) as an unavoidable impurity relative to zirconium dioxide.
[0198] <Formula (X)>
[0199] ([mass of hafnium oxide] / ([mass of zirconium dioxide]+[mass of hafnium oxide]))×100(%)
[0200] The maximum and minimum values of the contents of each component shown in the following examples are independent of the contents of other components and should be regarded as the preferred minimum and preferred maximum values of the present invention.
[0201] Furthermore, the maximum and minimum values of the measured values shown in the following examples are independent of the content (composition) of each component and should be regarded as the preferred minimum and maximum values of the present invention.
[0202] [Fabrication of Zirconium Composite Oxides]
[0203] (Example 1)
[0204] <First Process>
[0205] 92 g (35 g as ZrO2) of zirconium oxychloride octahydrate was dissolved in ion-exchanged water and mixed with 200 g (20 g as Y2O3) of yttrium chloride solution. The mixture was prepared with a total concentration of ZrO2 and Y2O3 of 5 w / v (mass volume percentage) based on oxides.
[0206] 25% by mass of NaOH was added to the prepared solution (yttrium-zirconium salt mixed solution) to obtain a composite hydroxide (YSZ precursor) containing Zr and Y. After filtration and washing, the YSZ precursor was heated to 150°C in an autoclave and subjected to 5×10⁻⁶ cycles. 5 YSZ precursor slurry was obtained by maintaining a pressure of Pa for 60 minutes.
[0207] It should be noted that, based on the feeding ratio, the YSZ precursor contains 23 mol% yttrium.
[0208] <Second Process>
[0209] Subsequently, a mixed solution of zirconium salt solution (ZrO2 concentration 25 w / v%) and 50 g of 25% sodium sulfate was dropped into the YSZ precursor slurry at 120 °C and maintained for 15 minutes. The zirconium salt solution was a solution in which 45 g (17 g as ZrO2) of zirconium oxychloride octahydrate was dissolved in ion-exchanged water. The solution was then cooled to obtain a reaction solution containing basic zirconium sulfate.
[0210] <Third Process>
[0211] Next, 200g (20g as CeO2) of cerium nitrate solution, 50g (5g as Nd2O3) of neodymium nitrate solution, and 50g (5g as Pr6O3) of cerium nitrate solution were added to the reaction solution containing basic zirconium sulfate. 11 A 5g praseodymium nitrate solution was prepared, and 25% sodium hydroxide was added until the pH reached above 13, thereby generating a hydroxide precipitate (a slurry containing zirconium hydroxide).
[0212] The obtained hydroxide precipitate was filtered and thoroughly washed with water, and then dried at 105°C for 24 hours. The dried hydroxide was then heat-treated (calcined) at 700°C in air for 5 hours to obtain the oxide. The obtained oxide was crushed in a mortar to obtain the zirconium composite oxide of Example 1. Table 1 shows the composition of the zirconium composite oxide calculated based on the feed ratio.
[0213] (Examples 2 to 9)
[0214] Except for adjusting the proportions of materials added in the first, second, and third steps to achieve the composition ratios described in Table 1, the zirconium composite oxides in Examples 2 through 9 were obtained in the same manner as in Example 1. It should be noted that in Examples 2 and 7, lanthanum nitrate solution was further added in the third step to achieve the composition ratios described in Table 1. In Example 9, phosphoric acid solution was further added in the third step to achieve the composition ratios described in Table 1.
[0215] (Comparative Example 1)
[0216] 182 g (70 g as ZrO2) of zirconium oxychloride octahydrate was dissolved in ion-exchanged water. The acid concentration was then adjusted to 0.67 N using 35% hydrochloric acid and ion-exchanged water, and the ZrO2 concentration was 4 w / v%. The resulting solution was placed in an autoclave and the pressure was set to 2 × 10⁻⁶. 5Pa was heated to 120°C, and 1035 g of 5% sodium sulfate was added at this temperature, which was then maintained for 15 minutes. After chlorination with sulfuric acid, the mixture was cooled to room temperature to obtain a slurry containing basic zirconium sulfate. To the slurry containing basic zirconium sulfate, 199 g (20 g as CeO2) of cerium nitrate solution, 75 g (7.5 g as Nd2O3) of neodymium nitrate solution, and 25 g (as Pr6O3) of sodium sulfate were added. 11 A praseodymium nitrate solution (approximately 2.5 g) was added. Then, 500 g of 25% sodium hydroxide was added over 60 minutes. This neutralization produced zirconium hydroxide. The zirconium hydroxide-containing slurry was then filtered, washed with water, and calcined at 700°C for 5 hours to obtain the oxide.
[0217] (Comparative Example 2)
[0218] Except for adjusting the material ratios to achieve the composition ratios described in Table 1, zirconium composite oxides were obtained in the same manner as in Comparative Example 1. It should be noted that yttrium nitrate solution was added instead of neodymium nitrate solution to achieve the composition ratios described in Table 1.
[0219] [Determination of specific surface area before heating]
[0220] The specific surface area of the zirconium composite oxides of the Examples and Comparative Examples was determined by the BET method using a specific surface area meter (manufactured by "Macsorb" MOUNTECH). The results are shown in Table 1.
[0221] [Determination of specific surface area after heating at 1000℃ for 3 hours]
[0222] For the zirconium composite oxides of the Examples and Comparative Examples, they were heated at 1000°C for 3 hours under atmospheric pressure (0.1013 MPa) and in an air atmosphere. The specific surface area of the zirconium composite oxides after heating at 1000°C for 3 hours was measured in the same manner as in "Determination of Specific Surface Area Before Heat Treatment". The results are shown in Table 1.
[0223] [Determination of specific surface area after heating at 1100℃ for 3 hours]
[0224] For the zirconium composite oxides of the Examples and Comparative Examples, they were heated at 1100°C for 3 hours under atmospheric pressure (0.1013 MPa) and in an air atmosphere. The specific surface area of the zirconium composite oxides after heating at 1100°C for 3 hours was measured in the same manner as in "Determination of Specific Surface Area Before Heat Treatment". The results are shown in Table 1.
[0225] [Determination of specific surface area after heating at 1200℃ for 3 hours]
[0226] For the zirconium composite oxides of the Examples and Comparative Examples, they were heated at 1200°C for 3 hours under atmospheric pressure (0.1013 MPa) and in an air atmosphere. The specific surface area of the zirconium composite oxides after heating at 1200°C for 3 hours was measured in the same manner as in "Determination of Specific Surface Area Before Heat Treatment". The results are shown in Table 1.
[0227] [Determination of specific surface area after heating at 1200℃ for 10 hours]
[0228] For the zirconium composite oxides of the Examples and Comparative Examples, they were heated at 1200°C for 10 hours under atmospheric pressure (0.1013 MPa) and in an air atmosphere. The specific surface area of the zirconium composite oxides after heating at 1200°C for 10 hours was measured in the same manner as in "Determination of Specific Surface Area Before Heat Treatment". The results are shown in Table 1.
[0229] [Determination of specific surface area after heating at 1250℃ for 10 hours]
[0230] For the zirconium composite oxides of the Examples and Comparative Examples, they were heated at 1250°C for 10 hours under atmospheric pressure (0.1013 MPa) and in an air atmosphere. The specific surface area of the zirconium composite oxides after heating at 1250°C for 10 hours was measured in the same manner as in "Determination of Specific Surface Area Before Heat Treatment". The results are shown in Table 1.
[0231] [Determination of pore volume before heating]
[0232] The pore volume and pore diameter were determined using the "Belsorp mini II" measuring device (manufactured by MicrotracBEL) and the BJH method.
[0233] The total pore volume was calculated using the obtained pore distribution. The results are shown in Table 1.
[0234] [Determination of pore volume after heating at 1250℃ for 10 hours]
[0235] For the zirconium composite oxides of the Examples and Comparative Examples, they were heated at 1250°C for 10 hours under atmospheric pressure (0.1013 MPa) and in an air atmosphere. The specific surface area of the zirconium composite oxides after heating at 1250°C for 10 hours was measured in the same manner as in "Determination of Specific Surface Area Before Heat Treatment". The results are shown in Table 1.
[0236] Particle size D 50 [Determination]
[0237] 0.15 g of zirconium composite oxide (powder) from the examples and comparative examples and 40 ml of 0.2% sodium hexametaphosphate aqueous solution were placed in a 50 ml beaker and dispersed for 5 minutes using an ultrasonic homogenizer "Digital Sonifier 450" (manufactured by Branson). The dispersion was then measured in an apparatus (laser diffraction particle size distribution measuring device "SALD-2300" manufactured by Shimadzu Corporation, Japan). The results are shown in Table 1.
[0238]
Claims
1. A zirconium composite oxide, characterized in that, include: Yttrium oxide of 5% to 50% by mass, and Cerium oxide, The specific surface area after heating at 1250℃ for 10 hours is 3.0 m². 2 / g or more 20.0m 2 / g or less; The pore volume is between 0.4 ml / g and 1.0 ml / g; The particle size D of the zirconium composite oxide 50 The range is from 0.1μm to 100μm.
2. The zirconium composite oxide according to claim 1, characterized in that, The yttrium oxide content is less than 40% by mass.
3. The zirconium composite oxide according to claim 1 or 2, characterized in that, The content of cerium oxide is more than 5% by mass and less than 50% by mass.
4. The zirconium composite oxide according to claim 1 or 2, characterized in that, It includes one or more oxides selected from rare earth elements other than cerium and yttrium.
5. The zirconium composite oxide according to claim 4, characterized in that, The oxide is one or more oxides selected from the group consisting of lanthanum oxide, neodymium oxide, and praseodymium oxide.
6. The zirconium composite oxide according to claim 5, characterized in that, The content of lanthanum oxide is more than 1% by mass and less than 30% by mass.
7. The zirconium composite oxide according to claim 5, characterized in that, The neodymium oxide content is more than 1% by mass and less than 30% by mass.
8. The zirconium composite oxide according to claim 5, characterized in that, The content of praseodymium oxide is more than 1% by mass and less than 30% by mass.
9. The zirconium composite oxide according to claim 1 or 2, characterized in that, It contains stabilized zirconium oxide, wherein the stabilized zirconium oxide contains more than 20 mol% and less than 30 mol% of yttrium oxide.
10. The zirconium composite oxide according to claim 1 or 2, characterized in that, The specific surface area after heating at 1200℃ for 10 hours is 12.0 m². 2 / g or above 40.0m 2 / g or less.
11. The zirconium composite oxide according to claim 1 or 2, characterized in that, The zirconium composite oxide is an oxygen storage material for a catalyst used in waste gas purification.
12. A method for manufacturing a zirconium composite oxide according to any one of claims 1 to 11, characterized in that, include: The first step is to obtain a composite hydroxide containing Zr and Y, which is at more than 20 mol% and less than 30 mol% as oxides; The second step involves mixing a mixture of sulfuric acid chlorinating agent and zirconium salt solution with the composite hydroxide to obtain a reaction solution containing basic zirconium sulfate. as well as In the third step, a cerium salt solution or compound is added to the reaction solution containing basic zirconium sulfate.
13. The method for manufacturing zirconium composite oxide according to claim 12, characterized in that, The third step includes: further adding a salt solution or compound of one or more metals selected from rare earth elements other than cerium and yttrium to a reaction solution containing basic zirconium sulfate.
Citation Information
Patent Citations
Composition based on oxides of zirconium, cerium and lanthanum and of yttrium, gadolinium or samarium, with high specific surface and reducibility, preparation method and use as a catalyst
EP2024084A1
Compositions based on zirconium oxides, cerium oxides, yttrium oxides, lanthanum oxides and other rare earth oxides, processes for their preparation and their use as catalysts
JP2009526729A
High porosity cerium- and zirconium-containing oxides
JP2017532278A
Cerium-and zirconium-based mixed oxides
US20190134608A1
Cerium oxide and zirconium oxide based composite rare earth oxide with favorable ageing resistance and high reduction activity and preparation method of cerium oxide and zirconium oxide based composite rare earth oxide
CN103191712A
